Socio-psychological model of psychoeducation for the population experiencing war trauma - CHORNA, Lidiia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
Background. Based on the generalization of global experiences in overcoming the consequences of large-scale emergencies on mental health and well-being, as well as intervention models for addressing more localized individual health issues found in psychological literature, a socio-psychological model of psychoeducation for the population affected by war trauma has been developed. The aim of psychological education should be to cultivate psychological resilience within the population, particularly in the context of the Russian-Ukrainian war, to support the preservation of Ukraine's statehood and achieve victory against the Russian aggressor.Methods. The analysis of scientific literature on the research topic, classification, and theoretical modeling concerning the organization and implementation of psychological education for the population.Results. The foundational principles included in psychological education are substantiated, such as: employing a resilient approach based on personal resources, preventing the adverse effects of war-related traumatic events, and adopting a trauma-sensitive approach in social interactions, which includes spreading awareness about mental trauma. The principles for organizing psychological education involve utilizing socio-psychological mechanisms of human social behavior to effectively integrate psychoeducation into practice; viewing psychological knowledge as a text aimed at mass communication; and presenting psychological knowledge to the population as a valuable tool for addressing life challenges. The methodological component of the model entails applying a technological approach to mastering basic psychological knowledge and skills that foster human resilience during war and advance the psychological literacy of the population.Conclusions. The proposed model of psychoeducation for those experiencing war trauma serves as the conceptual foundation for practical research on implementing psychological education within mass communication and social interaction processes in society subjected to potential trauma. The model treats psychoeducation as a distinct socio-psychological process and, based on the criteria of scientific novelty, is original regarding the mechanisms for developing the population's psychological literacy.
Keywords: psychoeducation; mental health; trauma; war; resilience; psychological literacy